Pengaruh Pemberian Konsentrat Mengandung Eucheuma Cottonii Afkir Terhadap Konsumsi dan Kecernaan Karbohidrat dan Glukosa Darah Sapi Bali Betina Muda yang Mengonsumsi Pakan Dasar Silase Rumput Alam atau Fodder Jagung - Arianto, Timoteus; Benu, Imanuel; Ernawati, Luh Sri (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aimed to determine the effect of concentrate containing fermented Eucheuma cottonii on carbohydrate intake, digestibility, and blood glucose levels in young female bali cattle. The study used a 4x4 Latin square design with four treatments: 60% Natural Grass Silage + 40% E. cottonii Concentrate Without Fermentation, 60% Natural Grass Silage + 40% E. cottonii Concentrate With Fermentation, 60% Corn Fodder + 40% E. cottonii Concentrate Without Fermentation, and 60% Corn Fodder + 40% E. cottonii Concentrate With Fermentation. The results showed that carbohydrate intake ranged from 2138.75 to 3813.13 g/head/day, while blood glucose levels ranged from 78.43 to 120.00 mg/dl. Concentrate containing fermented E. cottonii reduced carbohydrate intake (P<0.05) but did not affect carbohydrate digestibility or blood glucose levels. Overall, fermented E. cottonii concentrate did not improve feed intake performance or digestibility.